Pembrolizumab Utilization and Outcomes for Advanced Melanoma in US Community Oncology Practices - Cowey, C. Lance (J Immunother, 2018)
The programmed death-1 inhibitor pembrolizumab has demonstrated efficacy and safety in clinical trials for treating advanced (unresectable/metastatic) melanoma. We investigated the real-world utilization of pembrolizumab and associated patient outcomes for advanced melanoma in US community oncology practices. This retrospective, observational study used deidentified data from electronic health records for adult patients with advanced melanoma who received pembrolizumab at The US Oncology Network sites from September 2014 through December 2015, with follow-up through September 2016. Patients enrolled in clinical trials were excluded. Overall survival (OS) and physician-stated progression-free survival (PFS) were analyzed from pembrolizumab initiation using Kaplan-Meier, and associations between pembrolizumab therapy and OS/PFS, using multivariable Cox regression. Of 168 patients studied, 110 (65%) were male; the median age was 66 years (range, 26–over 90). Pembrolizumab was prescribed as first-line, second-line, and third-line/later for 39 (23%), 87 (52%), and 42 (25%) patients, respectively. In total, 41 patients (24%) had brain metastases. At pembrolizumab initiation, 21/129 (16%) had Eastern Cooperative Oncology Group performance status (ECOG PS) >1; 51/116 (44%) had elevated lactate dehydrogenase. Median follow-up was 10.5 months (range, 0–25.1); median OS was 19.4 months (95% confidence interval, 14.0–not reached); median PFS was 4.2 months (95% confidence interval, 2.9–5.3). Brain metastases, ECOG PS>1, elevated lactate dehydrogenase, and third-line/later (vs. first-line) pembrolizumab were significant predictors (P<0.01) of decreased survival. Treatment-related toxicity was a discontinuation reason for 25% (29/117) of patients, and for 10 of these 29 patients (6% of the full-study cohort) treatment-related toxicity was the only reported reason. The real-world effectiveness and safety of pembrolizumab for advanced melanoma are consistent with clinical trial findings.